ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) - Vikaliana, Resista; Br Barus, Eva RosaLinda (Prodi Teknik Industri, Fakultas Teknik, 2024)
This study analyzes the raw material inventory control of wood at PT Suryamas Lestariprima using the Economic Order Quantity (EOQ) method to achieve inventory cost efficiency. The results show that the EOQ calculation produces an optimal order quantity of 19.8772 m³ for durian wood, 18.8571 m³ for rambung wood, and 14.0553 m³ for miscellaneous wood, designed to minimize the company’s inventory costs. Additionally, the determination of safety stock at 14.954,5081 m³ for durian wood, 17.101,8334 m³ for rambung wood, and 384,7911 m³ for miscellaneous wood helps the company handle potential demand fluctuations during the lead time. This study also establishes the reorder point as the minimum threshold before reordering, namely 15.038,4718 m³ for durian wood, 17.230,6429 m³ for rambung wood, and 404.1126 m³ for miscellaneous wood. The application of the EOQ method results in inventory cost savings of IDR 5,409,005,289 for durian wood, IDR 2,888,543,167 for rambung wood, and IDR 1,506,367,701 for miscellaneous wood. Based on these findings, it is recommended that the company consider implementing EOQ as a standard in managing inventory to maintain operational efficiency.